(untitled) (Journal of Information Technologies in Education (ITE), 2013)
The problems associated with the need to fill the educational space of Ukraine electronic educational resources with appropriate quality in paper considers. Need to find new ways to provide access for teachers of secondary schools of electronic educational resources is justified.